An Evaluation of the Distribution, Scope, and Impact of Community Pharmacy Foundation Grants Completed by Academic Principal Investigators between 2002 and 2014 - Brian Isetts; Anthony W Olson, PharmD; Anne Marie Kondic; Jon Schommer (University of Minnesota Libraries Publishing, 2017)
Objective: From a total of 107 grants, a subset evaluation of 58 grants awarded to and completed by pharmacy faculty by the Community Pharmacy Foundation (CPF) from 2002 through 2014 was conducted to: (a) evaluate the representativeness across principal investigator (PI) academic institutions, (b) compare the scope of CPF grants completed by academic PIs across time, and (c) compare the impact of CPF grants completed by academic PIs across time. Methods: Quantitative data for all 107 CPF grants awarded between 2002 and 2014 were obtained from the CPF website and CPF personnel. Qualitative ethnographic data was generated from principal investigator (PI) interviews by email communications. All 107 grants, including a subset of 58 grants awarded to pharmacy faculty, were analyzed and compared between 'Initial Years' (2002-2008) and 'Recent Years' (2009-2014) using descriptive statistics for quantitative data and an extraction of dominant themes from PI reflections for qualitative data. Results: In the initial years (2002-2008), 54% of grants awarded to pharmacy faculty were from public academic institutions. This proportion increased to 80% in recent years (2009-2014). In recent years, pharmacy faculty projects were increasingly focused on higher AHRQ Impact Categories, such as changing policies and programs, clinical care and practice patterns, and health outcomes (AHRQ Impact Levels 2-4), rather than simply adding to the knowledge base (Impact Level 1). Academic investigators reported that funding positively influenced practice development (59%), promotion & advancement (59%), and expanded collaborations (38%). Diverse geographic representation of funding recipients was achieved. Conclusions: CPF funding has been invaluable for investigators seeking experience securing grant funding. And the impact of CPF funding has transitioned from studies that add to the knowledge base only, toward studies that effect actual health outcomes or that profoundly change practice. Conflict of Interest Anne Marie Kondic is Executive Director and Grants Administrator for the Community Pharmacy Foundation.   Type: Original Research